Evaluation of Safety Compliance of Nigerian Small Scale Metal Fabrication Workshops - Onwuka Osinachi Stanley; Nwankwojike Bethrand Nduka; Onuekwusi Chinemerem Ikechukwu (Academy Journal of Science and Engineering)
This study assessed the level of compliance of Nigerian small-scale metal fabrication workshops to the provisions of Occupational Health and Safety Regulations in order to ascertain the major causes of incessant accidents in this sector. Descriptive statistical tools were used to compare the safety practices in forty-four small scale metal fabrication workshops sampled from Nigeria to the Occupational Health and Safety Regulations (O.H.S.R) for metal fabrication workplace under the ‘FOUR Ps’(Premises, Plant and Materials, Procedures and People). Results revealed 3.86% and 84.09% as the mean availability/usage and non-availability of appropriate protective equipment in these workshops respectively. Also, less than 34% of the workshops sampled were 50% compliant to basic workshop safekeeping practices while none was up to 70% compliant. This shows that the use of protective equipment and adherence to safety precautions in these fabrication workshops is very poor. The nonchalant attitude of the owners of these workshops toward safety practices and inadequate supervision by regulatory agencies constitute the major reasons for this observed practice, hence, the incessant workplace accidents and negative cost-time overrun in this sector.